Policies of the two Christian orders in japan’s history on several arguments between the jesuits and franciscans - Xizi Chen (Trans/Form/Ação)
The different interpretations of Rome’s policies and the varied ways of apostolic work seem to be the reason for the unending tensions and conflicts between the Jesuits and Franciscans in Japan’s history of Christianity. However, politics also play an essential part in that situation upon closer examination. Behind the two Christian orders were two rival maritime powers, namely Portugal and Spain. The national sentiments of their fellow citizens might sometimes prevail over the interests of the mission in Japan. The Patronatus missionum issued by Rome yet intensified the conflicts and made the situation worse and irreversible, which eventually caused heavy loss to the whole mission. This thesis will paraphrase the following arguments between the Jesuits and Franciscans for a better understanding. The first and the most inciting one is commerce, the second is the separation of the parish, the third is apostolic approaches, and the last is practical policies. It is also worth mentioning that the situation seems not yet to be improved even after the “Twenty-six Martyrs” in Nagasaki, and the tension between the Jesuits and Franciscans grows into endless accusations against each other.